Socioscientific Issues-based Guided-inquiry E-worksheet on Optical Instruments Topic - Febriani, Febriani; Ibnusaputra, M.; Pradana, Pramudya Wahyu; Jumadi, Jumadi (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2022)
be taught in the learning process. This difficulty can be overcome by using learning media in the learning process. This study aimed to determine the feasibility of a guided-inquiry Electronic Student Worksheet based on SSI on the topic of optical instruments. The method used in this research is Research and Development (R&D) with 4D steps. At the define stage, it is done by studying literature and conducting short interviews with one physics teacher, design stage contains for lesson plans and electronic student worksheets; the developmentstage contains product validation activities by four experts and preliminary field testing by 23 students of class XI MIPA SMA Negeri 4 Yogyakarta, dissemination stage contains product distribution. The results of this study are 1) the SSI-based guided-inquiry Electronic Student Worksheet was developed by the objectives, context, and visual aspects, 2) the lesson plan and also the Electronic Student Worksheet are in the very valid category and can be used in the range of 93.75%-100%, and 3) The results of the preliminary field testing are in the valid category, with a range of 77.17%-79-35%. The conclusion is that the Product produced in this study was declared feasible. Hence, the implication of this research is that the resulting product can be used later by the teacher to help the learning process of the optical instrument topic.